Clinical Impact of the Current WHO Classification of Pituitary Adenomas - Saeger, W.; Honegger, J.; Theodoropoulou, M.; Knappe, U. J.; Schöfl, Christof; Petersenn, S.; Buslei, R. (Endocrine Pathology, 2016)
WHO classifications should be used for comparing the results from different groups of pathologist and clinicians by standardized histopathological methods. Our present report describes the important parameters of pituitary adenoma pathology as demand of the WHO classification for correlation to endocrine data and prognosis. The combination of HE stain based structures with immunostainings for pituitary hormones allows subclassification of adenomas as the best method not only for correlations to clinical hyperfunctions but also for statements to the sensitivity of drug therapies (somatostatin analogs, dopamine agonists). GH-, PRL- and ACTH-secreting pituitary adenomas are further classified based on the size and number of their secretory granules by electron microscopy, or as is mostly the case nowadays by cytokeratin staining pattern, into densely and sparsely granulated. Granulation pattern may be considered for the prediction of treatment response in patients with GH-secreting adenomas, since the sparsely granulated subtype was shown to be less responsive to somatostatin analog treatment. For prognosis, it is important to identify aggressive adenomas by measurements of the Ki-67 index, of the number of mitoses, and of nuclear expression of p53. Among the criteria for atypical adenomas, high Ki-67 labeling index and invasive character are the most important adverse prognostic factors. Promising molecular markers have been identified that might supplement the currently used proliferation parameters. For defining atypical adenomas in a future histopathological classification system, we propose to provide the proliferative potential and the invasive character separately.
EVALuna2:7318